2022
DOI: 10.3389/fbioe.2022.953590
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the mechanobiology of cornea: From bench side to the clinic

Abstract: The cornea is a transparent, dome-shaped structure on the front part of the eye that serves as a major optic element and a protector from the external environment. Recent evidence shows aberrant alterations of the corneal mechano-environment in development and progression of various corneal diseases. It is, thus, critical to understand how corneal cells sense and respond to mechanical signals in physiological and pathological conditions. In this review, we summarize the corneal mechano-environment and discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 154 publications
(263 reference statements)
1
4
0
Order By: Relevance
“…Biglycan also interacts with type VI collagen ( Wiberg et al, 2002 ), strongly causally implicated in CRF determination by our present analysis and that of rare coding variants ( van Hout et al, 2020 ) and both implicated in regulating ECM stiffness and maximal load ( Leiphart et al, 2021 ). The anchoring of cells to the ECM via bridging interactions is thought to play a critical role in mechanosensing and signaling, processes that have not been previously highlighted in the context of CRF or keratoconus GWAS interpretations but recognized important players in cornea biology ( Yang et al, 2022 ), and potential drivers of keratoconus pathology ( Dou et al, 2022 ). Among its multiple roles, THBS4 has been shown to influence trafficking of sarcoglycans in myocytes ( Brody et al, 2018 ), but the function of the specific isoform modulated by causal splicing variant highlighted by our study remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Biglycan also interacts with type VI collagen ( Wiberg et al, 2002 ), strongly causally implicated in CRF determination by our present analysis and that of rare coding variants ( van Hout et al, 2020 ) and both implicated in regulating ECM stiffness and maximal load ( Leiphart et al, 2021 ). The anchoring of cells to the ECM via bridging interactions is thought to play a critical role in mechanosensing and signaling, processes that have not been previously highlighted in the context of CRF or keratoconus GWAS interpretations but recognized important players in cornea biology ( Yang et al, 2022 ), and potential drivers of keratoconus pathology ( Dou et al, 2022 ). Among its multiple roles, THBS4 has been shown to influence trafficking of sarcoglycans in myocytes ( Brody et al, 2018 ), but the function of the specific isoform modulated by causal splicing variant highlighted by our study remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Rubbing action triggers several mechanical insults, including IOP spikes, altered shear stress, and high hydrostatic tissue pressure. For instance, vigorous rubbing can skyrocket the IOP to more than 10 times of a normal resting IOP, generating more dramatic pressure strain on the cornea ( 7 ). Mechano-transducers like YAP in stromal cells and β-catenin in epithelial cells are associated with the regulation of substrate stiffness and protease production in KC ( 42 , 43 ).…”
Section: Disorder Of Biomechanical Homeostasis In Ocular Diseasesmentioning
confidence: 99%
“…Starting with the anterior compartment, the cornea is the outermost component of the eye globe. Exposed to the open air, the cornea directly bears the exterior stimuli generated by atmospheric pressure ( 7 ), eye movement ( 8 ), and tear film motion ( 9 ), etc. To counterbalance, the internal stresses were fostered by aqueous humor ( 10 ) and IOP ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the physical cues of the cellular environment guide stem cell fate [33][34][35]. It is also suggested that biomechanical changes in the limbal stromal niche affect hLESCs fate [36]. No less importantly, mechanical and environmental changes in the corneal tissue have implications for some corneal diseases and pathologies [37].…”
Section: Introductionmentioning
confidence: 99%